LATGALIAN COMPONENT IN THE LEARNING OF LATVIAN LANGUAGE AND LITERATURE: FROM PRESCHOOL TO SECONDARY SCHOOL (1990–2015) - Vulāne, Anna; Stikute, Elita (Via Latgalica, 2017)
The conditions of language development and preservation are the quality of its acquisition in the early childhood, in-depth usage and study in the educational process and formation of positive and responsible attitude towards language and national literary heritage. The quality of the development of child’s Latvian language is determined by several environmental factors: the language environment in the family, the language environment in preschool, basic and secondary educational institutions and the language environment in public space.In Latgale most children learn Latvian in heterogeneous sociolinguistic environment. Child’s acquisition of the Latvian language in the family occurs in one of the following ways: in the native dialect (variant of dialect), if all the family members communicate only in one of our dialects, the High Latvian dialect; in the Latvian standard language, if the family members communicate in the standard language; in the so-called “third variant”, if the communication is in the Latvian standard language with a strong dialectal influence; or bilingually (dialect – Latvian standard language, dialect – Lithuanian, Polish, Russian, Belarusian or some other language, Latvian standard language – Lithuanian, Polish, Russian, Belarusian or some other language).Experience acquired during the project “Latvian Language in Monolingual and Bilingual Acquisition: tools, theories and applications” (LAMBA) shows that a part of our High Latvian dialect-speaking parents found it difficult to answer MacArthur-Bate Communicative development test questions, which were formed according to the Latvian standard language system. As communication with children takes place only in their native dialect, there are differences between child’s speech and the standard language at phonological and morphological level. At the same time, parents, after consultation on how to complete the test, noted that the quality of learning Latvian at school is better than learning at home where incorrect colloquial Latvian is used. Latvian language users in other parts of Latvia faced a similar problem, but in general it did not seriously affect the performance of the test. Students emphasize that more knowledge about interrelation between the Latvian dialectal and standard language would make the Latvian language acquisition process easier and help avoid interference of the native dialect. Language learning at school takes place in a monolingual environment, but some schools offer optional courses also in the Latgalian written (standard) language and literature. Outside the classroom, communication goes on in both, standard Latvian and native dialect and other languages.Language environment of the public space is heterogeneous; children hear different High Latvian variants as well as the so-called “third variant” which causes the most harm, both to Latgalian and Latvian standard languages and other languages. Taking into consideration the fact that two traditions of the written language have historically developed in Latvia – the Latvian standard language, and the Latgalian standard language tradition – and the Latgalian standard language is a very important component of Latgale regional and cultural identity and significant cultural value of Latvia, State Language Law 3 (4) determines that “the State ensures the preservation, protection and development of the Latgalian standard language as a historical option of the Latvian language”. Language knowledge, its usage in the learning process and the knowledge of literary and cultural heritage in close connection with national values are preconditions of language development and retention. Therefore, it is important that the school curricula and literature contain both Latvian and Latgalian. This report focuses, firstly, on how the school curricula and learning standards reflect the necessity to form and develop the Latgalian standard language and literature, secondly, how these issues are revealed in the text books of the Latvian language and literature developed from 1990 to 2015 and thirdly, it deals with secondary school students’ survey results on the knowledge of the Latgalian standard language and literature. Analysis of the standards and curricula of the primary school and secondary school subject “Latvian language” and “Literature” reveals that neither the Latgalian standard language as an option of the Latvian language, nor fiction written in the Latgalian standard language are reflected in text books. The text books developed during the last 20 years deal with these thematic issues only sporadically.